Analisis Manajemen Risiko Operasional Dalam Industri Perbankan - Rohid Akbar; Gilang Dwi Prasetyo; Muhammad Deary; Arsyadona A (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research emphasizes the importance of operational risk management in the Indonesian banking industry to maintain financial stability. Using a qualitative methodology and descriptive design, this research analyzes the implementation of risk management based on literature studies and official documents from OJK. The results show that effective risk management involves identifying, measuring, monitoring and controlling the risks faced by banks. Improved human resource competencies and implementation of good corporate governance principles are required to overcome challenges in risk management. Recommendations are provided to strengthen risk management practices, expected to contribute to the health of the banking sector and national economic growth.